An Attempt to Correct Erroneous Ideas Among Teacher Education Students: The Effectiveness of Refutation Texts - Ferrero, Marta; Konstantinidis, Emmanouil; Vadillo, Miguel A. (Frontiers in Psychology, 2020)
There is sound evidence about the high prevalence of misconceptions about education among pre-service teachers. This trend continues after students complete the degree in education and once they are in the exercise of their profession. In fact, several studies show that these misconceptions are widespread among in-service teachers. Erroneous ideas about education may divert material and human resources to poor grounded methods and teaching tools, compromising the quality of education. Strategies to debunk misconceptions among future teachers, who may not have a firm position about many educational issues, might contribute to reverse this trend. The main goal of the present study was to assess the efficacy of refutation texts in the correction of misconceptions among pre-service teachers. As in previous studies with in-service teachers, refutation texts were effective in reducing participants’ endorsement of misconceptions. But this effect was short-lived and did not affect participants’ intention to use educational methods that are based on the misconceptions addressed in the refutation texts.